Numerical model of solidification of cast composite with particles = Model numeryczny krzepnięcia kompozytu z cząstkami - Ciesielski, Mariusz; Domański, Zbigniew; Mochnacki, Bohdan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the paper the numerical model of heat transfer in non-homogeneous domain (cast composite) is considered. The composite is formed by the spherical particles (Pb) and the metal matrix (Al). Initial temperatures of components correspond to solid state (particle) and liquid one (matrix).
Keywords: kompozyt; krzepnięcie; model matematyczny krzepnięcia; cast composite; solidification; numerical modelling; control volume method